The Potential of Low-Temperature Solar Industrial Process Heat Applications in Cyprus - Kalogirou, Soteris A. (My University, 2004)
In this paper an overview of the potential of low-temperature solar industrial process heat applications is presented. The temperature requirements considered range from 60°C to 90°C. The characteristics of low to medium temperature solar collectors that can be employed are given and an analysis of the efficiency and cost of the solar systems is presented. Based on TRNSYS simulations, an estimation of the solar contribution of solar process heat plants operating in Cyprus are given for different collector technologies. The annual energy gains of such systems are from 745 to 994 kWh/m2-a and the resulting energy costs obtained for solar heat are from 0.025 to 0.043 Euro/kWh depending on the collector type applied. The costs will even be more favourable if the solar collectors become cheaper and renewable energy subsidies are considered.
Keywords: Heat applications; Solar industrial process; Cyprus